Understanding financial management as a determining factor for the success of MSMEs: A qualitative study - Meileginta Kaban (International Journal of Accounting and Management Information Systems, 2024)
Purpose: This study aims to explore the understanding of financial management among micro, small, and medium enterprises (MSMEs) and how such understanding influences the success and sustainability of their business. The primary focus is to identify the key financial management factors considered essential by MSME owners and the challenges they face in implementing effective financial practices. Research/methodology: This research employs a qualitative literature review methodology to analyze relevant studies, reports, and articles related to MSME financial management. This study synthesizes insights from various sources to provide a comprehensive understanding of the current practices, challenges, and factors that contribute to the financial success of MSMEs. Results: The findings indicate that a solid understanding of financial management, including cash flow management, transaction recording, and long-term financial planning, is crucial for MSME success. Despite the recognition of its importance, many MSME owners face barriers such as a lack of financial knowledge, limited access to financial resources, and reliance on manual accounting methods. Moreover, many fail to engage in long-term financial planning, which impedes their ability to manage risks and plan for business expansion effectively. Conclusions: Understanding financial management is vital for MSME success. However, limited literacy, resources, and manual practices hinder effective implementation, highlighting the need for targeted support and education. Limitations: This study is limited to a qualitative literature review, which may not capture the full range of experiences of MSME owners across different sectors or regions. Contribution:. This research provides valuable insights for MSME owners, financial institutions, and policymakers to understand the critical role of financial literacy and provide better support for MSMEs.